2007 2nd Bio-Inspired Models of Network, Information and Computing Systems 2007
DOI: 10.1109/bimnics.2007.4610080
|View full text |Cite
|
Sign up to set email alerts
|

Virus spread in complete bi-partite graphs

Abstract: In this paper we study the spread of viruses on the complete bi-partite graph KM;N . Using mean …eld theory we …rst show that the epidemic threshold for this type of graph sati…es c = 1 p M N , hence, con…rming previous results from literature. Next, we …nd an expression for the average number of infected nodes in the steady state. In addition, our model is improved by the introduction of infection delay. We validate our models by means of simulations. Inspired by simulation results, we analyze the probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this vein, we showed that our protocol can also be used to spread other kinds of information within the system. tion of viruses on a complete bipartite graph [32]. Their mathematical model is able to predict the probability of spread accurately.…”
Section: Resultsmentioning
confidence: 99%
“…In this vein, we showed that our protocol can also be used to spread other kinds of information within the system. tion of viruses on a complete bipartite graph [32]. Their mathematical model is able to predict the probability of spread accurately.…”
Section: Resultsmentioning
confidence: 99%